2021
DOI: 10.30516/bilgesci.839844
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salicylic Acid on Triticale under Salt Stress

Abstract: The goal of this study was to determine the effect of salicylic acid (50 µM) on triticale grown under salt stress. In this study, we investigated shoot and root lengths, malondialdehyde, proline, ion leakage, relative water content, chlorophyll content. The results indicated that salicylic acid is quite effective to deal with salt stress. Anatomically shoot (3%) and root lengths (4%), as well as relative water content (12%) and chlorophyll content (9%), were increased by salicylic acid under salt toxicity by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Among the potential endogenous hormones, salicylic acid (SA), and thiourea (TU) has been marked assuming a very noteworthy role in plant growth and development and impact a wide assortment of plant physiological processes, ion uptake and transportation, proline metabolism, and plant water relations by minimizing salt toxicity under stress situations (Wakchaure et al, 2018;Kaya et al, 2019). The shoot and root length, chlorophyll content, relative water content was found to increase whereas malondialdehyde, proline and ion leakage were decreased after application of SA in Triticale under saline condition (Erkan and Aras Aşci 2021). Furthermore, both TU and SA serve as a critical signalling molecule for counteracting the negative effects of ROS induced oxidative stress by the enhancement of antioxidant enzyme activity such as CAT, APX, and POD (Patade et al, 2012;Yadu et al, 2017;Kaya et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the potential endogenous hormones, salicylic acid (SA), and thiourea (TU) has been marked assuming a very noteworthy role in plant growth and development and impact a wide assortment of plant physiological processes, ion uptake and transportation, proline metabolism, and plant water relations by minimizing salt toxicity under stress situations (Wakchaure et al, 2018;Kaya et al, 2019). The shoot and root length, chlorophyll content, relative water content was found to increase whereas malondialdehyde, proline and ion leakage were decreased after application of SA in Triticale under saline condition (Erkan and Aras Aşci 2021). Furthermore, both TU and SA serve as a critical signalling molecule for counteracting the negative effects of ROS induced oxidative stress by the enhancement of antioxidant enzyme activity such as CAT, APX, and POD (Patade et al, 2012;Yadu et al, 2017;Kaya et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, both TU and SA serve as a critical signalling molecule for counteracting the negative effects of ROS induced oxidative stress by the enhancement of antioxidant enzyme activity such as CAT, APX, and POD (Patade et al, 2012;Yadu et al, 2017;Kaya et al, 2020). In addition, numerous reports demonstrated that salt stress caused a significant increase in MDA content on rice and maize which was prevented by SA treatments (Erkan & Aras Aşci, 2021;Pandey et al, 2021). Several previous studies also reported that priming with exogenous SA and TU was found to mitigate the salt stress in rice (Oryza sativa), onion (Pisum sativum), potato (Solanum tuberosum), faba bean (Vicia faba), mung bean (Vigna radiata), and lentil (Lens culinaris) by intensifying the activities of antioxidant enzymes and osmotic adjustment and by promoting root and shoot formation and by stimulating flowering (Mani et al, 2012;Mostofa & Fujita 2013;Khan et al, 2014;Ahmad et al, 2017;Nooren et al, 2017;Nie et al, 2018;El-Kinany, 2020;Yadav et al, 2020;Pandey et al, 2021).…”
Section: Introductionmentioning
confidence: 99%